Modeling the temperature dependence of the density oscillation of energy states in two-dimensional electronic gases under the impact of a longitudinal and transversal quantum magnetic fields - Erkaboev, U. I.; Rakhimov, R. G.; Sayidov, N. A.; Mirzaev, J. I. (Indian journal of physics, 2023)
At present, the interest in applied and fundamental research in the field of condensed matter physics has shifted from bulk materials to nanoscale semiconductor structures. Of particular interest are the properties of the energy spectrum of charge carriers in low-dimensional semiconductor structures exposed to a quantizing magnetic field. Quantization of the energy levels of free electrons and holes in a quantizing magnetic field leads to a significant change in the form of oscillations of the density of energy states in two-dimensional semiconductor structures. Thus, in this manuscript, we investigated the effect of the temperature and thickness of the quantum well on the oscillations of the density of energy states in the conduction band of nanoscale semiconductor structures. A new mathematical model has been developed for calculating the temperature dependence of the oscillations of the density of states in a rectangular quantum well under the influence of a transverse quantizing magnetic field. Using the proposed model, the experimental results were explained at different temperatures and magnetic fields.